Design and beam dynamic simulation of the thermionic RF electron gun with external resonant cavity for transverse emittance reduction - C. Saisa-ard (2019)
© 2019 Elsevier B.V. The accelerator components and radiation production systems at the PBP-CMU Electron Linac Laboratory of the Plasma and Beam Physics Research Facility are currently being developed and upgraded to make it possible for generation of the mid-infrared free-electron laser (MIR FEL) and the coherent intense terahertz (THz) radiation via transition radiation and superradiant undulator radiation. To generate a high brightness radiation, a high quality electron beam is crucially required. One of the important keys for this issue is the good performance and reliable electron source. Development of a new thermionic radio-frequency (RF) electron gun is foreseen at our facility. The design of the new RF gun was conducted with the aim to reduce transverse emittance while keeping the longitudinal phase space distribution that is suitable for the bunch compression with the alpha magnet. The present design of the PBP-CMU RF electron gun, which has 1-1/2 cell TM010 reentrant cylindrical standing-wave resonant cavities and a side-coupling cavity, was used as the starting model for this work. The shape and dimensions of the new RF gun were optimized and the electromagnetic field distribution was simulated by using the program CST Microwave Studio 2016. Electron beam dynamic simulations were done with program ASTRA. The initial particle distribution from thermionic emission process was created by using the self-developed MATLAB script that provides the thermal emittance values corresponding well to the theoretical values. The results of this work suggest that by adding an external resonant cavity with a rounded pill-box shape to the present RF gun model can reduce the transverse emittance. This additional cavity has an optimal length of 25 mm and is connected to the present RF gun at the position 13 mm downstream the second cavity exit. The RF wave is coupled from the second cavity to the external cavity via the second side-coupling cavity. The entire structure finally has a resonant frequency of 2856.03 MHz, an unloaded quality factor of 15623 and a shunt impedance of 1.18 MΩ. The maximum electric field values in the first, the second and the external cavity are 32.8, 65.0 and 29.8 MV/m, respectively. The results from beam dynamic simulations show that this new design RF gun should be able to produce electron bunches with a charge of 170 pC per bunch, a maximum kinetic energy of 2.72 MeV and an energy spread of 540 keV. The simulated horizontal and vertical normalized emittances of 90% beam were respectively reduced by 11.6% and 4.5% compared to the values obtained from the original PBP-CMU RF gun. Furthermore, it was found that the transverse emittance is conserved at the distance longer than 60 cm downstream the external cavity exit.